Heidegger's analytic : interpretation, discourse, and authenticity in Being and time - Carman, Taylor, 1965- (Modern European philosophy., 2003)
This book offers a new interpretation of Heidegger's major work, Being and Time. Unlike those who view Heidegger as an idealist, Taylor Carman argues that Heidegger is best understood as a realist. Rigorous, jargon-free and deftly argued this book will be necessary reading for all serious students of Heidegger.